A Critical Review of Oxazolidinones: An Alternative or Replacement for Glycopeptides and Streptogramins? - George G Zhanel; Coleen Schroeder; Lavern Vercaigne; Alfred S Gin; John Embil; Daryl J Hoban (Canadian Journal of Infectious Diseases, 2001)
OBJECTIVE: To review the available data on the oxazolidinones linezolid and eperezolid.